Evaluation of the otorhinolaryngology consultations requested from the emergency department - Atalay, Fatma; Topal, Kubra (Annals of Medical Research, 2022)
Aim: In this study, the aim was to examine the otorhinolaryngology consultations requested from the emergency service and to discuss the results in light of the literature. Materials and Methods: In our study, 376 patients who were admitted to emergency department and who were consulted to the otorhinolaryngology outpatient clinic of Kastamonu Training and Research Hospital between the dates 01.10.2019 and 01.10.2021 were examined retrospectively. The age and gender of patients, date of consultation, reasons for consultation, diagnoses made as a result of consultation, and interventions taken were recorded. Results: 142 (37.8%) of the patients for whom consultations were requested were female and 234 (62.2%) were male. The mean total age was 38.43. The most common reason for consultation was nasal fracture, infectious causes, foreign body in the ear and foreign body in the nose, respectively (n=77, 20.47%; n=51, 13.56%; n=39, 10.37%; n=36, 9.57%). The most frequently consultation requested months are July (n=62, 16.48%), August (n=45, 11.96%) and September (n=44, 11.70%), respectively. As a result of the consultations, the most common interventions were foreign body removal and nasal fracture repositioning (n=64, 17.02%; n=58, 15.42%). No otorhinolaryngology pathology was found in 79 patients (21.01%). Conclusion: The fact that emergency physicians have sufficient knowledge and experience in otorhinolaryngology emergencies will both reduce the mortality and morbidity of patients and prevent the loss of time and internal power by preventing unnecessary consultation requests.